Topology-Controlled Metallamacrocyclic Assemblies Containing Ni2+ and Alkali Metal Ions with Catechol-Scaffolding Aroylbis(N,N-Diethylthiourea) - Dang Hung Pham; Minh Hai Nguyen; Van Ha Nguyen; Canh Dinh Le; Ulrich Abram; Hung Huy Nguyen; Chien Thang Pham (My University, 2025)
Topology-Controlled Metallamacrocyclic Assemblies Containing Ni2+ and Alkali Metal Ions with Catechol-Scaffolding Aroylbis(N,N-Diethylthiourea)
Keywords: Ni2+